Clinical course of primary HIV infection: consequences for subsequent course of infection. Issue 6692 (15th July 1989) - Pedersen, C.; Lindhardt, B. O.; Jensen, B. L.; Lauritzen, E.; Gerstoft, J.; Dickmeiss, E.; Gaub, J.; Scheibel, E.; Karlsmark, T.
Abstract : OBJECTIVE–To investigate the impact of the clinical course of the primary HIV infection on the subsequent course of the infection. DESIGN–Prospective documenting of seroconversion, follow up at six month intervals, and analysis of disease progression by life tables. PATIENTS–86 Men in whom seroconversion occurred within 12 months. PRIMARY OUTCOME MEASURE–Progression of HIV infection, defined as CD4 lymphocyte count less than 0.5 X 10(9)/l, recurrence of HIV antigenaemia, or progression to Centers for Disease Control group IV. MAIN RESULTS–Median follow up was 670 (range 45-1506) days. An acute illness like glandular fever occurred in 46 (53%) subjects. Three year progression rates to Centers for Disease Control group IV was 78% at three years for those who had longlasting illnesses (duration greater than or equal to 14 days) during seroconversion as compared with 10% for those who were free of symptoms or had mild illness. All six patients who developed AIDS had had longlasting primary illnesses. Three year progression rates to a CD4 lymphocyte count less than 0.5 X 10(9)/l and to recurrence of HIV antigenaemia were significantly higher for those who had longlasting primary illnesses than those who had no symptoms or mild illness (75% v 42% and 55% v 14%, respectively). CONCLUSION–The course of primary infection may determine the subsequent course of the infection.